The significance of autopsy in the technological development and team building of colorectal surgery - Liu Hailong; Jiang Huihong; Ding Haibo; Lin Moubin (结直肠肛门外科)
This article reviews the role of autopsy in the technological development of colorectal surgery through a literature review, introduces the relevant experience of the authors’ team in conducting autopsy research, and further explores the significance of autopsy in the team building of colorectal surgery. Additionally, it discusses several issues that colorectal surgeons should pay attention to when conducting anatomical research. This article summarizes the important role of autopsy in the development of colorectal surgery from various aspects and provides an outlook for future research directions.